A critical thermal transition driving spring phenology of Northern Hemisphere conifers. Issue 6 (11th December 2022) - Huang, Jian‐Guo; Zhang, Yaling; Wang, Minhuang; Yu, Xiaohan; Deslauriers, Annie; Fonti, Patrick; Liang, Eryuan; Mäkinen, Harri; Oberhuber, Walter; Rathgeber, Cyrille B. K.; Tognetti, Roberto; Treml, Václav; et al.
Abstract: Despite growing interest in predicting plant phenological shifts, advanced spring phenology by global climate change remains debated. Evidence documenting either small or large advancement of spring phenology to rising temperature over the spatio‐temporal scales implies a potential existence of a thermal threshold in the responses of forests to global warming. We collected a unique data set of xylem cell‐wall‐thickening onset dates in 20 coniferous species covering a broad mean annual temperature (MAT) gradient (−3.05 to 22.9°C) across the Northern Hemisphere (latitudes 23°–66° N). Along the MAT gradient, we identified a threshold temperature (using segmented regression) of 4.9 ± 1.1°C, above which the response of xylem phenology to rising temperatures significantly decline. This threshold separates the Northern Hemisphere conifers into cold and warm thermal niches, with MAT and spring forcing being the primary drivers for the onset dates (estimated by linear and Bayesian mixed‐effect models), respectively. The identified thermal threshold should be integrated into the Earth‐System‐Models for a better understanding of spring phenology in response to global warming and an improved prediction of global climate‐carbon feedbacks. Abstract : We identified a threshold temperature at 4.9°C for the onset of xylem cell‐wall‐thickening, using a unique dataset covering 20 coniferous tree species in the Northern Hemisphere, along a broad mean annual temperature gradient (‐3.05 to 22.9°C). We observed a critical thermal transition that the advancement of tree xylem phenology driven by rising temperature would significantly decline above this threshold temperature. The thermal transition also separates the Northern Hemisphere conifers into cold and warm thermal niches, with MAT and spring forcing being the primary drivers for the onset of xylem cell‐wall‐thickening, respectively.